2001
DOI: 10.1067/mva.2001.118581
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of color-flow Doppler scanning, power Doppler scanning, and frequency shift for assessment of carotid artery stenosis

Abstract: CD and PD carotid artery stenosis measurements are highly reproducible, and in our hands provided accuracy equal to PSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 20 publications
0
29
1
Order By: Relevance
“…Overestimation of the vessel lumen and underestimation of the length of a stenosis as a result of pulsation and reverberation artefacts known from CCDS also occur in PD in preocclusive stenoses. Nevertheless, comparative studies indicate that sonographic diagnostics of high-degree stenoses are improved by using PD [20,22].…”
Section: Discussionmentioning
confidence: 96%
“…Overestimation of the vessel lumen and underestimation of the length of a stenosis as a result of pulsation and reverberation artefacts known from CCDS also occur in PD in preocclusive stenoses. Nevertheless, comparative studies indicate that sonographic diagnostics of high-degree stenoses are improved by using PD [20,22].…”
Section: Discussionmentioning
confidence: 96%
“…We used planimetry to diagnose carotid restenosis of 50% to 69% because it provides an angiographic-like carotid stenosis measurement, with a good sonographic-angiographic agreement. [12][13][14][15][16][17][18] In addition, although there is a good agreement for severe stenosis between velocity parameters and planimetric data obtained by angiography or carotid ultrasound, 9,19,20 moderate stenoses are quantified less accurately by velocity parameters, 21 particularly in the setting of a multicenter study, which potentially increases variability of velocity measurements between centers. 9 In our study, the observed proportion of positive agreement between velocity and planimetric data were poor for the category of 50% to 69% restenosis (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the diameter measurements, too, depend on the investigator. Our own experience indicates that blooming artifacts do not occur in B-flow and that the color coding of the grey tones mostly anticipates the effect of contrast medium enhancement [32]. When there are circular calcifications, all US modalities encounter constraints: in some cases, areas of residual flow can be detected in the B-flow cross-section that can otherwise be demonstrated only after administering US contrast media with the CCDS and PD.…”
Section: Discussionmentioning
confidence: 97%